2005
DOI: 10.1509/jimk.13.1.36.58538
|View full text |Cite
|
Sign up to set email alerts
|

Market Orientation, Relationship Marketing Orientation, and Business Performance: The Moderating Effects of Economic Ideology and Industry Type

Abstract: This study examines how economic ideology and industry type moderate the impacts of market orientation and relationship marketing orientation on business performance. The authors collected data through a survey of firms in both Mainland China and Hong Kong. They selected these two economies because they have similarities in cultural dimensions and differences in economic dimensions. The authors find support for the moderating effect of economic ideology and industry type on the link among market orientation, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
4
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 58 publications
7
121
4
1
Order By: Relevance
“…On the other hand, the results of other studies on how market orientation influences performance are not so conclusive, suggesting that market orientation does not directly influence firm performance but rather impacts performance via other mediating variables (Sin, Tse, Yau, Chow, & Lee, 2005;Singh, 2009). Furthermore, some studies found positive and significant relationships (Julian, 2010) while other studies reported insignificant relationships when performance was measured via alternative measures of performance, for example, market share (Baker & Sinkula, 2005).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, the results of other studies on how market orientation influences performance are not so conclusive, suggesting that market orientation does not directly influence firm performance but rather impacts performance via other mediating variables (Sin, Tse, Yau, Chow, & Lee, 2005;Singh, 2009). Furthermore, some studies found positive and significant relationships (Julian, 2010) while other studies reported insignificant relationships when performance was measured via alternative measures of performance, for example, market share (Baker & Sinkula, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…Although many studies have attempted to measure market orientation differently when examining its empirical relationship with different measures of performance most previous research has either adopted the measures developed by Narver andSlater (1990) (e.g., Grinstein, 2008;Hooley, Fahy, Greenley, Beracs, Fonfara, & Snoj 2003;Sin et al, 2005;Singh, 2009) or that of Kohli & Jaworski (1990) (e.g., Baker & Sinkula, 2005Kyriakopoulos & Moorman, 2004;Racela, Chaikittisilpa, & Thoumrungroje, 2007). Kohli and Jaworski (1990) were, arguably, the pioneers of market orientation research.…”
Section: Introductionmentioning
confidence: 99%
“…Por un lado, varios autores tratan de introducir el componente relacional en la base teórica tradicional sobre la orientación estratégica de la empresa. Partiendo de la consideración de que el marketing relacional conlleva que "la empresa esté activamente involucrada en la creación, desarrollo y mantenimiento de intercambios comprometidos, interactivos y beneficiosos con ciertos agentes de interés" (Harker 1999, p. 16), una corriente de investigadores utilizan el concepto "orientación de marketing relacional" para referirse a aquellas empresas que optan por la adopción de un enfoque estratégico que promueva dichos resultados (Sin et al 2005). Por otro lado, algunos autores promueven la incorporación del enfoque basado en el conocimiento en esta visión relacional.…”
Section: La Orientación Al Mercado De La Redunclassified
“…On the one hand, several authors have attempted to introduce the relational component into the traditional theoretical basis of firms' strategic orientation. Based on the consideration that relational marketing implies that "the firm is proactively involved in the creation, development and maintenance of committed, interactive and beneficial exchanges with certain agents of interest" (Harker, 1999: 16), several researchers have used the "relational marketing orientation" concept to refer to firms adopting a strategic focal point which promotes such performance (Sin et al, 2002(Sin et al, , 2005Tse et al, 2004). On the other hand, some authors have incorporated the knowledge-based approach into this relational vision by attempting to apply market orientation concept used in the firm's domain in a network context (Elg, 2002(Elg, , 2003Evanschitzky, 2007;Helfert, Ritter and Walter, 2002;Langerak, 2001;Siguaw, Simpson and Baker, 1999).…”
Section: Network Market Orientationmentioning
confidence: 99%